Early Intraarticular Injection of Hyaluronic Acid Attenuates Osteoarthritis Progression in Anterior Cruciate Ligament-Transected Rats - Tsai, Wei-Yuan; Wu, Jia-Lin; Liu, Chih-Chung; Cherng, Chen-Hwan; Tsai, Ru-Yin; Jean, Yen-Hsuan; Wong, Chih-Shung (Connective tissue research, 2013)
Subject: Hyaluronic acid (HA) is widely used to relieve the symptoms of osteoarthritis (OA). An association of reduction of glutamate content with the synovial fluid of OA rats was reported previously. Design: Anterior cruciate ligament transaction (ACLT) was performed on one knee in male Wistar rats, the other knee was assigned to sham control and HA or saline was injected intraarticularly into the ACLT knee from week 3 to week 7. Knee dialysate was collected for amino acid measurement at week 20. Morphology and histopathology of the femoral medial condyles and synovium were examined and evaluated using Mankin and synovitis scores. Results: HA injection provided better cartilage (3.38 ± 0.03 vs. 5.45 ± 0.0.02) and synovial condition (3 ± 0.02 vs. 6.03 ± 0.02) than saline controls. Moreover, HA injection reduced the concentration of glutamates in knee dialysates compared to saline controls (1.11 ± 0.14-folds and 2.21 ± 0.19-folds of the sham-operated knee, respectively). Cystine/glutamate antiporter system expression was significantly downregulated in the saline group, but not in the HA group (0.32 ± 0.08-folds and 0.71 ± 0.10-folds of the sham-operated knee, respectively). Conclusion: Early intraarticular injection of HA attenuates the progression of cartilage destruction in the ACLT knee, and the downregulation of the cystine/glutamate antiporter system was accompanied by the progression of OA.